MODERN APPROACHES TO TREATMENT OF CHILDREN WITH CHRONIC GASTRODUODENITIS DURING RECOVERY - M.M. Gurova; V.A. Afans'ev; S.V. Zuev (Union of pediatricians of Russia, 2007)
The «Multitabs immuno kids» vitamin and mineral complex application increases the treatment efficacy, conduces to the correction of the trophologic status, maintains the endoecosystem of the macroorganism, normalizes the metabolic processes and improves the quality of the patients' live among the children with chronic gastroduodenites during recovery.Key words: chronic gastroduodenites, vitamin and mineral complex, children.